Differential actions of orexin receptors in brainstem cholinergic and monoaminergic neurons revealed by receptor knockouts: implications for orexinergic signaling in arousal and narcolepsy - Kohlmeier, Kristi A.; Tyler, Christopher J.; Kalogiannis, Mike; Ishibashi, Masaru; Kristensen, Morten P.; Gumenchuk, Iryna; Chemelli, Richard M.; Kisanuki, Yaz; Yanagisawa, Masashi; Leonard, Christopher S. (Frontiers in Neuroscience, 2013)
Orexin neuropeptides influence multiple homeostatic functions and play an essential role in the expression of normal sleep-wake behavior. While their two known receptors (OX1 and OX2) are targets for novel pharmacotherapeutics, the actions mediated by each receptor remain largely unexplored. Using brain slices from mice constitutively lacking either receptor, we used whole-cell and Ca2+ imaging methods to delineate the cellular actions of each receptor within cholinergic (laterodorsal tegmental nucleus; LDT) and monoaminergic (dorsal raphe; DR and locus coeruleus; LC) brainstem nuclei – where orexins promote arousal and suppress REM sleep. In slices from OX2-/- mice, orexin-A (300 nM) elicited wild-type responses in LDT, DR and LC neurons consisting of a depolarizing current and augmented voltage-dependent Ca2+ transients. In slices from OX1-/- mice, the depolarizing current was absent in LDT and LC neurons and was attenuated in DR neurons, although Ca2+-transients were still augmented. Since orexin-A produced neither of these actions in slices lacking both receptors, our findings suggest that orexin-mediated depolarization is mediated by both receptors in DR, but is exclusively mediated by OX1 in LDT and LC neurons, even though OX2 is present and OX2 mRNA appears elevated in brainstems from OX1-/- mice. Considering published behavioral data, these findings support a model in which orexin-mediated excitation of mesopontine cholinergic and monoaminergic neurons contributes little to stabilizing spontaneous waking and sleep bouts, but functions in context-dependent arousal and helps restrict muscle atonia to REM sleep. The augmented Ca2± transients mediated by both receptors appeared mediated by influx via L-type Ca2+ channels, which is often linked to transcriptional signaling. This could provide an adaptive signal to compensate for receptor loss or prolonged antagonism and may contribute to the reduced severity of narcolepsy in single receptor knockout mice.